2013
DOI: 10.1016/j.jval.2013.08.331
|View full text |Cite
|
Sign up to set email alerts
|

Cost Analysis of a Fibrin Sealant Patch for Mild, Moderate and Problematic Soft Tissue Surgical Bleeding: A Hospital Perspective

Abstract: for sensitivity analyses showed cost-savings ranging from € 22,525 to € 996,384 of prophylaxis with aPCC vs. on-demand with rFVIIa. ConClusions: Three times/ week aPCC prophylaxis could reduce 16% the total treatment cost of severe HA with inhibitor, saving up to € 98,000/patient/year.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“… 27 , 36 A recent economic evaluation also showed that this new fibrin sealant patch was predicted to be cost saving in problematic surgical bleeding for hospital stakeholders due to hospital resources averted, such as transfusions and bleeding retreatment, versus standard of care. 37 Such results are particularly relevant in light of the findings of the current study showing significantly greater hemostat costs in uncontrolled bleeding cohorts. Several additional new hemostatic agents have also been developed that are currently undergoing clinical trials.…”
Section: Discussionmentioning
confidence: 72%
“… 27 , 36 A recent economic evaluation also showed that this new fibrin sealant patch was predicted to be cost saving in problematic surgical bleeding for hospital stakeholders due to hospital resources averted, such as transfusions and bleeding retreatment, versus standard of care. 37 Such results are particularly relevant in light of the findings of the current study showing significantly greater hemostat costs in uncontrolled bleeding cohorts. Several additional new hemostatic agents have also been developed that are currently undergoing clinical trials.…”
Section: Discussionmentioning
confidence: 72%